SEBS/ PS, SIS/ PS ve SBR/ PS polimer karışımlarının ayakkabı taban malezemesi olarak üretilmesi ve özelliklerinin incelenmesi - Uluğ, Ebru (My University, 2011)
SEBS/ PS, SIS/ PS VE SBR/ PS POLİMER KARIŞIMLARININ AYAKKABI TABAN MALZEMESİ OLARAK ÜRETİLMESİ VE ÖZELLİKLERİNİN İNCELENMESİ Ayakkabı taban malzemesi olarak çeşitli malzemeler kullanılmaktadır. Taban yapımında en önemli grubunu elastomerler oluşturmaktadır. Elastomerler çeşitli malzemelerle karıştırılarak özellikleri değiştirilebilir. Bu deneysel tez çalışmasında SEBS, SIS ve SBR türü elastomer malzemelere PS katılarak bir taban malzemesi hazırlanmıştır. Akış yönünde ve akış yönüne dik doğrultulardaki özellikleri tespit edilmiştir. Mikroyapı özellikleri SEM ve EDS ile belirlenmiştir. Bunlara ek olarak SEBS/ PS, SIS/ PS ve SBR/ PS polimer karışımlarının elastiklik modülü, akma mukavemeti, kopma mukavemeti, sertliği, Izod darbe mukavemeti, aşınma mukavemeti, erğime akış indisleri, vicat yumuşama sıcaklıkları ve ısıl çarpılma sıcaklıkları belirlenmiştir.

PRODUCTION AND INVESTIGATION OF PROPERTIES OF SEBS/ PS, SIS/ PS AND SBR/ PS POLYMER BLENDS: IN SHOE BASE MATERIAL Various materials have been used in production of shoe sole. The most of the material groups are shoe soles with elastomer based. Elastomers are usually mixed with different materials to increase the values of physical properties. In this study, the effect of PS on the mechanical, thermal and morphological properties of SEBS, SIS and SBR type elastomers -based shoe sole material was investigated in flow direction 0o and flow direction 90o. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, SEBS/ PS, SIS/ PS and SBR/ PS polymer blends were subjected to examinations to obtain their elasticity modulus, yield strengths, strength at break, elongation at break, hardness, izod impact strength, wear rate, melt flow index (MFI), vicat softening point and heat deflection temperature (HDT).
Keywords: Ayakkabı, Üretim; Metal Eğitimi